2015
DOI: 10.1177/0091217415589297
|View full text |Cite
|
Sign up to set email alerts
|

Effects of religious and spiritual variables on outcomes in violent relationships

Abstract: Religious and spiritual factors were associated with most outcomes. Spiritual symptoms had a consistently negative effect on outcomes while use of spiritual resources had variable effects. Religious coping was only associated with refraining from leaving the relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…One hundred forty-three participants completed measures at baseline designed to assess background characteristics as well as factors that may affect the decision-making process. Prior work found that religious variables (Katerndahl, Burge, Ferrer, Becho, & Wood, 2015), awareness (Burke et al, 2001), depression and hope, childhood abuse, coping and violence appraisal, and partner’s controlling behaviors contribute to violence dynamics and outcomes, including health care utilization (Katerndahl, Burge, Ferrer, Becho, & Wood, 2014a). In addition to demographics, we assessed religiousness using three scales (seven questions) from the Brief Multidimensional Measure of Religiousness/Spirituality (public religious activities, private religious activities, religious intensity; Fetzer Institute/National Institute on Aging Working Group, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…One hundred forty-three participants completed measures at baseline designed to assess background characteristics as well as factors that may affect the decision-making process. Prior work found that religious variables (Katerndahl, Burge, Ferrer, Becho, & Wood, 2015), awareness (Burke et al, 2001), depression and hope, childhood abuse, coping and violence appraisal, and partner’s controlling behaviors contribute to violence dynamics and outcomes, including health care utilization (Katerndahl, Burge, Ferrer, Becho, & Wood, 2014a). In addition to demographics, we assessed religiousness using three scales (seven questions) from the Brief Multidimensional Measure of Religiousness/Spirituality (public religious activities, private religious activities, religious intensity; Fetzer Institute/National Institute on Aging Working Group, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…relationship with/still seeing perpetrator. (Drinnon, 2001) Domestic violence attributions (developed for study) The Intent to Return Questionnaire (developed for study) Katerndahl et al (2015) N = 200 women with history of physical DA.…”
Section: Study Selection and Data Collectionmentioning
confidence: 99%
“…The sense of survivorship that women identify as unique to their immigrant experience was clearly a source of strength for overcoming challenges related to being in an abusive relationship. Historically, underrepresented minorities, including immigrants, have found solace and a source of inner strength through their faith and beliefs (Ahmad et al, 2013; Katerndahl et al, 2015; Njie-Carr et al, 2012; Sabri, Simonet, & Campbell, 2018).…”
Section: Discussionmentioning
confidence: 99%